Surface characterisations and photocatalytic property of MWO 4 (M = Fe 2+, Co 2+, Ni 2+ ) nanoparticles. (16th January 2015) - He, H-Y.; Cao, L-Y.; He, Z.; Lu, J.
MWO4 (M = Fe 2+, Co 2+, Ni 2+ ) nanocrystalinee synthesised by a salt aqueous solution reaction show similar nanoparticle size, good ultraviolet-visible light absorption and narrow bandgap energy. The oxidation-reduction potential of methyl orange aqueous solution with initial pH = 5−7 is positively varied as presence of the nanoparticles in ultraviolet-visible light irradiation, which indicates an oxidative photocatalysis behaviour of the nanoparticles surfaces. The photodegradation rate of the methyl orange aqueous solution on the nanoparticles increases with increase in the light absorption and the oxidation-reduction potential. The ORP clearly also is a necessary and useful parameter in researches and applications of photocatalysis.